PENERAPAN MEDIA FLASHCARD UNTUK MENINGKATKAN PEMAHAMAN TERHADAP KALIMAT “I LIKE” DAN “I DON’T LIKE” PADA PELAJARAN BAHASA INGGRIS SISWA KELAS III SDN KARANGTUMARITIS 1 - Ade Dina Nurkhakiki; Putri Intan Syamsudin; Fadhil Abu Jihad; Juhdan Abdullah Mu’arif; Dewi Nopasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
English, as an international language, plays a crucial role in learning from elementary school. However, limited resources and limited exposure to foreign languages ​​often hinder learning. One approach teacher can take is to utilize visual media such as flashcards, which can help students understand vocabulary through concrete representations. This study aims to analyze the effectiveness of using flashcards in improving third-grade students' understanding of simple vocabulary and the sentence patterns "I like" and "I don't like." The study used a descriptive qualitative method with 41 students. Data were collected through observation, field notes, documentation, and pre- and post-learning tests. The results showed a significant improvement after the implementation of flashcards. Before the use of flashcards, only 3 students (±7.3%) were able to understand the vocabulary, while after the use of flashcards, this number increased to 38 students (±92.7%). Furthermore, students appeared more enthusiastic, easily remembered vocabulary, and were able to use it in simple sentences. The study's conclusions confirm that flashcards are effective in teaching English in elementary schools because they strengthen memory, increase motivation, and create an interactive learning environment. Keywords: Flashcard, English Learning, Vocabulary, Elementary School